Successful Combination Therapy of Acne Keloidalis Nuchae - Kartika Ruchiatan; Erfina Rohana Sormin; Reti Hindritiani; Asmaja Soedarwoto; Hendra Gunawan (Faculty of Medicine, Universitas Airlangga, 2017)
Background: Acne keloidalis nuchae (AKN) is a chronic, inflammatory, idiopathic disorder of hair follicle, characterized by keloidal papules or plaques on the nape and occipital scalp. Various therapies have been reported to treat AKN with various results. Purpose: To observe the efficacy of combination therapy for AKN. Case report: A 19-year-old man presented with multiple pruritic papules, 0.1–0.3 cm in diameter on the nape and occipital area. The histopathological examination revealed neutrophil, eosinophil, and plasma cell infiltration in infundibulum, which was consistent with AKN pathological patterns. Discussion: Combination therapy consisted of 0.025% tretinoin cream, 0.1% mometasone furoate cream, intralesional triamcinolone acetonide 5 mg/ml, and doxycycline 2x100 mg. The improvement was initially observed on 2nd week of follow up, as the lesions had reduced in size and number, and the improvement became more significant on 4th week of follow up. Conclusion: Combination therapy of topical tretinoin, topical and intralesional steroid, and systemic doxycycline shows good result and can be considered in the management of AKN.